2011
DOI: 10.1530/rep-11-0196
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the participation of TGFB superfamily signalling pathways mediating porcine and murine cumulus cell expansion

Abstract: It is widely held that mammalian cumulus cell (CC) expansion requires oocyte-paracrine signalling, however in three of the four species studied to date, CC expansion occurs in the absence of the oocyte. This study was conducted to examine the paracrine and SMAD/MAPK intracellular signalling mechanism mediating porcine CC expansion, and to compare these to the mouse. Cumulus-oocyte complexes (COCs) and oocyte-free complexes (OOXs) from pigs and eCG-primed mice were treated in vitro with FSH and a broad range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
(72 reference statements)
2
20
0
Order By: Relevance
“…Therefore, through this mechanism, the MAPK14 is involved in regulation of mouse cumulus expansion. Such a MAPK14-dependent regulatory loop seems to also work in the pig as indicated by results presented in this study and also in other studies reporting inhibition of pig cumulus expansion by SB203580 (Yamashita et al 2009, Gilchrist & Ritter 2011. In the mouse, FSH-but not EGF-induced cumulus expansion and elevation of expansion-related transcripts (Has2 and Ptgs2) required MAPK14 activity (Diaz et al 2006).…”
Section: Signaling In Pig Cumulus-oocyte Complexessupporting
confidence: 80%
“…Therefore, through this mechanism, the MAPK14 is involved in regulation of mouse cumulus expansion. Such a MAPK14-dependent regulatory loop seems to also work in the pig as indicated by results presented in this study and also in other studies reporting inhibition of pig cumulus expansion by SB203580 (Yamashita et al 2009, Gilchrist & Ritter 2011. In the mouse, FSH-but not EGF-induced cumulus expansion and elevation of expansion-related transcripts (Has2 and Ptgs2) required MAPK14 activity (Diaz et al 2006).…”
Section: Signaling In Pig Cumulus-oocyte Complexessupporting
confidence: 80%
“…In brief, cumulus-oocyte complexes were aspirated from small antral follicles (2-4 mm) and matured in protein-free porcine oocyte maturation basic IVM medium (35), supplemented for the first 22 h of IVM with 1 mM dibutyryl-cAMP and 100 ng/ml amphiregulin (R&D Systems) and treated with either vehicle (control), 20 or 100 ng/ml pro-cumulin, 20 or 100 ng/ml mature cumulin, 100 ng/ml pro-GDF9, 100 ng/ml pro-BMP15, or 100 ng/ml of each of pro-GDF9 ϩ pro-BMP15. Cumulus expansion was assessed at 22 h of IVM and scored as per standard criteria (36,37). At 22 h, cumulus-oocyte complexes were washed and matured for a further 22 h in porcine oocyte maturation without supplements or treatments (13,33,34).…”
mentioning
confidence: 99%
“…However, in three out of the four species studied to date, CCE did not require the presence of oocytes (Nagyova 2012;Watson et al 2012;Gharibi et al 2013). To study this process, Gilchrist and Ritter (2011) analysed the paracrine mechanisms of the Smad/MAPK signalling cascade comparing porcine and murine cumulus-oocytecomplexes (COCs). Treating COCs and oocyte-free complexes (OOXs) with FSH and TGFB superfamily antagonists, they found that the inhibition of TGFB superfamily genes, such as GDF9, TGFB, activin A, and activin B, and several BMP superfamily genes did not affect the CCE of porcine COCs.…”
Section: Tgfb Superfamily Gene Expression During Oogenesismentioning
confidence: 99%
“…Since Derynck et al (1985), first identified a partial amino acid sequence from transforming growth factor beta 1 (TGFB1) purified from blood platelets, numerous studies have highlighted the role of this peptide as a modulator of cell growth, proliferation and differentiation in many types of cells and tissues (Gilchrist and Ritter 2011;Nagamatsu et al 2012). It is also thought that TGF proteins are involved in the regulation of oocyte and embryonic growth and development.…”
Section: Introductionmentioning
confidence: 99%